Report on Evaluation of Framework of Appraisal of Projects A Study Undertaken for the PAMD, Planning Commission, Government of India by Indian Institute of Management, Bangalore - Planning Commission (Planning Commission, 2014)
The Planning Commission, Government of India, is the highest planning body in India and one of its important role is appraising large projects that are funded by the central government. It plays a crucial role in project appraisal by ensuring that the projects are within broad plan priorities and policies; the projects are technically sound; and financially appropriate. Planning Commission and, specifically the, Project Appraisal and Monitoring Division (PAMD) play a critical role ensuring independent and professional appraisal of large projects, especially the social sector projects.
Planning Commission Government of India
Planning Commission Government of India